Relação AST/ALT em cães, correlações bioquímicas séricas e valor prognóstico. - Ana Laysla Frota Machado (2021)
The relationship between the transaminases aspartate aminotransferase and alanine aminotransferase (AST/ALT), also known as the De Ritis ratio, is calculated based on the serum values of the activities of these enzymes. This relationship is widely used in human medicine to conduct differential diagnosis between liver diseases and extra hepatic diseases and to establish a prognosis. In Veterinary Medicine, its use is not common and its importance is still unknown. This study aimed to evaluate the De Ritis ratio in healthy dogs and in diagnoses of liver diseases and other extrahepatic diseases observed in the veterinary medical routine. A retrospective study was carried out, with data from 302 dogs from the Veterinary Hospital of UFMG, Belo Horizonte (MG), and who had biochemistry evaluation performed at the Laboratory of Veterinary Clinical Pathology, between the months of January and May 2019. Two experiments were conducted in a complementary manner, including “healthy” animals, “acute and chronic liver disease” and patients with extrahepatic diseases (pyometra, trauma/fractures, intoxication/poisoning, leishmaniasis, hemoparasitosis, and nephropathy). The results of serum hematological and biochemical tests were analyzed, evaluating the behavior of liver enzymes and averages of the AST/ALT ratio at two times, moment zero (M0) and 48 hours after M0 (M48). In the experiment 1, animals with acute liver disease presented ALT and AST mean activities well above the upper limit of the reference intervals for the specie. The AST/ALT ratio was inversely proportional to the gamma glutamyl transferase (GGT), ALT, alkaline phosphatase (ALP) and albumin. In the experiment 2, to assess the effect of the AST/ALT ratio on the outcome, a logistic regression model was adjusted to suit dichotomous data (live/death). To analyze the effect of treatment over time, the average of the AST/ALT ratio of the groups presented patients with results in M0 and M48 was calculated. Animals with chronic liver diseases had the greatest average of the AST/ALT ratio, and although only 19.74% of the animals were classified as having chronic liver disease, the findings of this study suggest that De Ritis ratio is more effective for their identification than acute liver diseases. The determination of the De Ritis ratio at moments M0 and M48 proved to be an important tool for the evaluation of the efficacy in the therapeutic approach adopted for the patient. Animals allocated to the “pyometra”, “intoxication/poisoning” and “fracture/trauma” groups presented higher averages for the AST/ALT ratio (2.67, 2.54, and 2.21, respectively). The correlation between the AST/ALT relatioship in serial evaluations (M0 and M48) and the prognostic response for survival, showed that when animals double De Ritis ratio from M0 to M48, they tend to have a probability 2.5 times greater of dying. Thus, it is concluded that the AST/ALT ratio should be included in the clinical routine and used to assess the evolution of the disease in dogs.